Nephrologic abnormalities in neonatal asphyxia at Cipto Mangunkusumo Hospital, Jakarta - Idham Amir; Vera M Manoe; Taralan Tambunan (Paediatrica Indonesiana, 2004)
Introduction Neonatal asphyxia is still the leading cause of highmorbidity and mortality in developed countries, as well as in devel-oping countries including Indonesia. As a response to asphyxia,renal hypoxia occurs which is initially temporary, but if persisting,can cause permanent damage to the cortex and medulla.Objective The purpose of this study was to determine thenephrologic abnormalities in neonatal asphyxia at CiptoMangunkusumo Hospital.Methods This was a cross sectional descriptive study conductedin the Division of Neonatology, Cipto Mangunkusumo Hospital fromAugust until November 2002. Neonates with congenital malforma-tion were excluded.Results The study showed that the incidence of nephrologic ab-normalities in neonatal asphyxia based on Apgar scores at 1, 5,and 10 minutes were 65/100, 26/33, and 5/6, respectively. The riskof nephrologic abnormalities was not statistically different in se-vere asphyxia compared to moderate asphyxia. Severe asphyxiaat 1 minute Apgar scores was correlated with the occurrence ofoliguria.Conclusion In asphyxiated newborn, it is very important to inves-tigate the possibility of nephrologic abnormalities